Fundamentals of abstract algebra - DeBonis, Mark J. (Boca Raton : CRC Press, 2024)
Fundamentals of Abstract Algebra is a primary textbook for a one year first course in Abstract Algebra, but it has much more to offer besides this. The book is full of opportunities for further, deeper reading, including explorations of interesting applications and more advanced topics, such as Galois theory. Replete with exercises and examples, the book is geared towards careful pedagogy and accessibility, and requires only minimal prerequisites. The book includes a primer on some basic mathematical concepts that will be useful for readers to understand, and in this sense the book is self-contained.
Includes references and index
Keywords: Algebra, Abstract; Group theory; Fields (Mathematics); Rings